Dogs Entering the United States from Rabies‐Endemic Countries, 2011–2012. (22nd September 2014) - Sinclair, J. R.; Washburn, F.; Fox, S.; Lankau, E. W.
Summary International dog imports pose a risk because of the potential movement of disease agents, including the canine rabies virus variant which has been eliminated from the United States since 2007. US regulations require a rabies vaccination certificate for dogs arriving from rabies‐endemic countries, but permit the importation of dogs that have not been adequately immunized against rabies, provided that the dogs are confined under conditions that restrict their contact with humans and other animals until they have been immunized. CDC Form 75.37, 'Notice to Owners and Importers of Dogs', explains the confinement requirements and serves as a binding confinement agreement with the importer. In this evaluation, we describe the characteristics of unimmunized dogs imported into the United States over a 1‐year period based upon dog confinement agreements recorded at the Centers for Disease Control and Prevention (CDC) quarantine stations. Confinement agreements were issued for nearly 2800 unimmunized dogs that entered the United States during 1 June 2011–31 May 2012, the majority of which travelled to the United States by air and without any seasonal pattern in import volume. Over 60% of these animals were puppies <3 months of age and included a wide variety of breeds. The dogs arrived from 81 countries, with the majority arriving from North America or Europe. Dogs placed on confinement agreements had final destinations in 49 states. California, New York, Texas, Washington and Florida received the largest number of dogs on confinement agreements. These results (which do not reflect human travel or US dog ownership data) suggest that a large portion of unimmunized dogs arrive from rabies‐endemic countries for commercial, shelter and rescue purposes. Further evaluation and key stakeholder involvement are needed to assess whether the current dog importation regulations are an adequate compromise between the benefits and risks of dog importation.